Advancing the Frontiers of Simulation A Festschrift in Honor of George Samuel Fishman - Alexopoulos, Christos; Goldsman, David; Wilson, James R. (International Series in Operations Research & Management Science, 2009)
This Festschrift honors George Samuel Fishman, one of the founders of the field of computer simulation and a leader in the disciplines of operations research and management science for the past five decades. The papers in this volume span the theory, methodology, and application of computer simulation. Renowned researcher, teacher, mentor, and author, Fishman has made fundamental contributions to both the theory and practice of simulation, the dissemination of knowledge, service to the profession, and the advancement of the status of the field. Among his many honors and awards are the Distinguished Service Award from TIMS/College on Simulation; the Frederick W. Lanchester Prize from INFORMS; and the INFORMS Simulation Society's Lifetime Professional Achievement Award. Individual papers in this volume include a biography and then an interview with Fishman; Computer Intensive Statistical Model Building; Patchwork Distributions; Asymptotic Validity of Batch Means Steady-State Confidence Intervals; Efficient Modeling of Delays in Discrete-Event Simulation; Sampling from Linear Multivariate Densities; Factor Screening in Simulation Experiments; and many others that all honor the achievements, influence, and friendship of George Samuel Fishman. .